Mathematical Playfulness: A Humorous Approach to Reforming English Orthography (Global Journal of Computer Science and Technology, 2024)
The desire to shorten texts to reduce the effort of writing has always been very popular Among others this has led to the invention and common use of stenography e g by secretaries However use of stenography is demanding a non-negligible learning effort Therefore people were looking for alternatives requiring much less learning expenditure An example for a completely different approach to shorten texts is represented by the kind of writing which is popular in particular among our current young generation e g when writing and sending SMS messages or eMails Here formulations such as CU or C U for see you U R for you are coffee 2 go for coffee to go tea 4 U for tea for you 2 4 1 for two for one etc are pretty common